Assesment of Coronary Artery Disease by The Detection of Inflammatory Marker Like Erythrocyte Sedimentation Rate, Neutrophil Lymphocyte Ratio and Leucocyte Count - Bhuiyan, Mohammad Monzurul Alam; Islam, Md Saiful; Ferdousi, Sheuli; Ghosh, Mousumi; Paul, Debatosh; Sultana, Tuhin; Hoque, Harisul; Rahman, Quddusur; Ahmed, AN Nashimuddin (University Heart Journal, 2015)
Background: The inflammatory marker like erythrocyte sedimentation rate (ESR), neutrophil lymphocyte ratio (NLR), total leucocyte count can be a useful tool to detect and measure the early detection of coronary artery disease (CAD). Objective: To assess the ESR, NLR and total leucocyte count as a useful inflammatory marker for detection of coronary artery disease (CAD). Methods: This case control study was conducted in the Department of Clinical pathology in collaboration with Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from March 2014 to February 2015. Total 134 patients were enrolled in this study who were waiting for further percutaneous coronary intervention (PCI) in the Department of Cardiology, BSMMU; 84 cases were considered as Group I (Patients with CAD) and 50 controls were Group II (Patients without CAD). Coronary artery disease with 50% coronary artery stenosis and more critical lesion that were diagnosed by percutaneous coronary intervention (PCI) were included in this study as cases. Coronary artery disease with less than 50% coronary artery stenosis who were diagnosed by percutaneous coronary intervention (PCI) were included in this study as control. The statistical analysis was done by Chi-square test and unpaired samplet test. Results: NLR and ESR was higher in CAD (+) group compared to group without CAD (-) (2.76 (±0.74) vs. 1.56 (±0.15), p<0.001) and (31.07± (18.25) vs. 11.76± (6.20), p<0.001).Conclusion: ESR and NLR was higher in patients with angiographically proven CAD compared to those without CAD. ESR and NLR may be a useful inflammatory marker to detect the presence of CAD. University Heart Journal Vol. 10, No. 2, July 2014; 55-59